2014
DOI: 10.1089/fpd.2013.1631
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofE. coliO157:H7 in Cultivable Soil by Fast and Slow Pyrolysis-Generated Biochar

Abstract: An exploratory study was performed to determine the influence of fast pyrolysis (FP) and slow pyrolysis (SP) biochars on enterohemorrhagic Escherichia coli O157:H7 (EHEC) in soil. Soil + EHEC (inoculated at 7 log colony-forming units [CFU]/g of soil) + 1 of 12 types of biochar (10% total weight:weight in soil) was stored at 22°C and sampled for 8 weeks. FP switchgrass and FP horse litter biochars inactivated 2.8 and 2.1 log CFU/g more EHEC than no-biochar soils by day 14. EHEC was undetectable by surface plati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 72 publications
(70 reference statements)
0
14
1
1
Order By: Relevance
“…MM-biochar, CS-biochar, and RS-biochar represent mushroom medium-based biochar, corn stalk-based biochar, and rice straw-based biochar, respectively phenols (e.g., phenol and 3-methyl-phenol) detected in CSbiochar, as their potential toxicity (Fritze et al 1998;Villar et al 1997) could inhibit the growth of the inoculant. Similarly, it was reported that some fast pyrolysis and slow pyrolysis biochar could inactivate enterohemorrhagic Escherichia coli O157:H7 in soil (Gurtler et al 2014). This hypothesis was further supported by the observation that when VOCs including phenols in CS-biochar were consumed by the inoculant during the incubation, the abundance of B. mucilaginosus in CS-biochar was higher than that in RS-biochar.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…MM-biochar, CS-biochar, and RS-biochar represent mushroom medium-based biochar, corn stalk-based biochar, and rice straw-based biochar, respectively phenols (e.g., phenol and 3-methyl-phenol) detected in CSbiochar, as their potential toxicity (Fritze et al 1998;Villar et al 1997) could inhibit the growth of the inoculant. Similarly, it was reported that some fast pyrolysis and slow pyrolysis biochar could inactivate enterohemorrhagic Escherichia coli O157:H7 in soil (Gurtler et al 2014). This hypothesis was further supported by the observation that when VOCs including phenols in CS-biochar were consumed by the inoculant during the incubation, the abundance of B. mucilaginosus in CS-biochar was higher than that in RS-biochar.…”
Section: Discussionmentioning
confidence: 89%
“…We tested the hypothesis that VOCs on fresh biochar may play a vital role in shaping the structure of soil microbial communities. Data suggest that some sorbed organic substances on biochar comprise a fraction of the VOCs that potentially could be toxic to some microbes and inhibit their growth (McClellan et al 2007;Gurtler et al 2014), and may shift the structure of soil microbial communities (Graber et al 2010). Although VOCs on biochar have been qualified (Spokas et al 2011;Hale et al 2012), their functions on the structure of soil microbial communities are not well clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar can both adsorb E. coli and its toxic metabolites already in the digestive tract, as well as reduce the spread of those bacteria in water and soil by adding it to manure. Gurtler et al (2014) investigated the effect of various biochar on the inactivation of E. coli O157: H7 (EHEC) when applied to soils. All biochars produced by either fast or slow pyrolysis from switchgrass, horse manure or hardwood significantly reduced EHEC concentrations, with fast pyrolysis of barley and oak log feedstock providing the best results in the contaminated soil mix, where EHEC after 4 weeks were untraceable using a cultivation based assessment (Gurtler et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Biochar, or at least some labile biochar compounds, were a potential source of organic matter, which could support carbon consumption and survival of some groups of microbes ( Ameloot et al, ). On the other hand, absorbed volatile organic compounds might be toxic and negatively affect soil microorganisms ( Gurtler et al, ). Therefore, negative, null or positive effects have been reported depending on the biochar employed and the soil type ( Liang et al, ).…”
Section: Discussionmentioning
confidence: 99%